USM IS ALWAYS READY TO OFFER EXPERTISE AND HELP TO DEVELOP PERLIS, SAYS VC - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 13 August 2016 – Universiti Sains Malaysia (USM) is always ready to offer its expertise and help including sharing its experiences and success stories with any party in Perlis.